NLRP1B is an integrated decoy that subverts Shigella flexneri E3 ligase activity to promote effector-triggered immunity - Siwon Chung; Hannah Hudson; Kaitlin A. Stromberg; Andrew Sandstrom (Proceedings of the National Academy of Sciences, 2026)
Inflammasomes are cytosolic immune complexes that recognize pathogen-associated stimuli to initiate a potent inflammatory response. While some inflammasomes directly recognize pathogen-associated molecules, others, such as the NLRP1B inflammasome, respond to pathogen-associated activities. Specifically, the NLRP1B inflammasome senses the enzymatic activity of pathogen-secreted proteases and E3 ligases through a mechanism of “functional degradation”—effectors that promote the proteasomal degradation of NLRP1B induce activation of this inflammasome. However, why pathogens would target NLRP1B for degradation when doing so promotes a robust inflammatory response is unclear. We propose that NLRP1 acts as an integrated decoy receptor by mimicking other host proteins targeted for degradation by pathogens. Specifically, we hypothesize that NLRP1B encodes sequences and features such that these pathogen effectors are unable to distinguish between NLRP1B and their other targets. To test this hypothesis, we determine how the Shigella flexneri E3 ligase IpaH7.8 is recognized by NLRP1B and whether these interactions are equivalent to those between IpaH7.8 and its other substrates, the Gasdermin (GSDM) family of proteins. Here, we show that IpaH7.8 recognizes both the GSDMs and NLRP1B through a single shared interface and that NLRP1B presents a surface similar to that recognized by IpaH7.8 on the GSDMs. In this way, NLRP1B acts as a decoy for the GSDMs to subvert the activity of IpaH7.8 to promote inflammasome activation. These data demonstrate that NLRP1B acts as an integrated decoy receptor and establish the use of integrated decoy receptors by the vertebrate immune system.